Gereja sebagai Hamba yang Melayani: Sebuah Perspektif Eklesiologi Transformatif di Era Society 5.0 - Bakhoh Jatmiko; Teguh Bowo Sembodo; Albert Yusuf Langke; Sukirdi Sukirdi; Yupiter Hulu (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2021)
Era Society 5.0 which focuses on the utilization of technology for human interest (human-centered); on one hand becomes a fresh air after in the previous era there was a lot of dehumanization due to the dominance of the development of digital technology, big data, artificial intelligence and automatization. On the other hand, this development is considered as the causalty of moral decadence, polarization, inequality and various forms of social problems that are massively increasing in the midst of society. In this context, how should the church play a role in implementing transformational mandat within the society? The Church is God's gift to the world to involve in serving the world’s problems. The Church presents as God’s compassion manifestation towards sinners and marginalized group of people who are exploited and dominated. This research approach used a descriptive qualitative method that involves historical and explorative studies of biblical texts and literature research. Historical studies were conducted to find the transformative role of the church throughout the history of human civilization history. An explorative-ecclesiological approach is used to synchronize the role of the church in the light of transformative ecclesiology. Historical studies in this study have found that in the church development history from the New Testament church, medieval ages to the reform era, the church was not only present to carry out the mandate of spiritual transformation; but also presented in addressing the daily life basis’ problems and advocating the fatalist groups in the midts of capitalists and paternaists’ oppression. The role of the church as a servant is a form of manifestation of the transformative mandate belongs to the church. As a servant the church must reflects the existence of Christ as a faithful Servant. The Church must follow, obbey the commandments, live the mission and have the ministry focus as Christ’s.